Terpenoids: A promising traditional chinese medicine for neuropathic pain relief - Hui-Si Yang; David H. Mauki; Yue-Xiang Zheng; Ting-Hua Wang; Xiu-Ying He (Pharmacological Research)
Neuropathic pain (NPP) is a prevalent chronic condition characterized by spontaneous pain, hyperalgesia, allodynia, and sensory abnormalities, severely impacting patients' quality of life. Despite various guided treatments, their clinical efficacy remains limited, often accompanied by adverse reactions. Traditional Chinese medicine (TCM) offers unique advantages in disease treatment through its holistic approach (balancing the body as a unified system) and syndrome differentiation principle (personalized medicine). Recent research has highlighted terpenoids for their analgesic effects and minimal side effects. This review summarizes the role of terpenoids in NPP and their underlying molecular mechanisms. Terpenoids, natural products found in plants, are categorized into monoterpenoids, sesquiterpenoids, diterpenoids, triterpenoids, and tetraterpenoids based on isoprene units. These compounds alleviate NPP by: inhibiting neuroinflammation and oxidative stress, regulating mitochondrial function, modulating ion channels, and influencing the cannabinoid and opioid receptor systems. This review aims to deepen our understanding of terpenoids and provide crucial evidence and mechanistic insights for their application in NPP therapy.